Application of IR Radiation in White Pepper Drying : A preliminary study - Ana Sakura, Zainal Abidin; Mohamad Syafiq Iylia, Jamadi; Nur Dzakirah, Bahri; Mohammad Omar, Abdullah; Annisa, Jamali; Sinin, Hamdan; Rasli, Muslimen; Zehnder, J.A.M. (Springer Nature, 2024)
This preliminary study was conducted to evaluate the potential of IR radiation in white pepper drying process. Insulated chamber test rig with 58 cm2 of opening for natural ventilation equipped with RS Pro ceramic infrared (IR) heating elements has been developed. The chamber operating temperature was set within 50-70oC with radiation intensity of 0.5 W/cm2 and wave-length of 5.3 μm. Tests were conducted using various platform distances from ceramic IR emitter (10, 15, 20, 25 and 30 cm). A single layer of soaked pepper berries (same initial amount of 50 gram) was placed on the platform in the closed chamber and exposed to IR radiation for 75 minutes. Weight of the sample was observed over the drying time. It was found that, the farthest gap (30 cm) showing the lowest weight loss. Meanwhile the shortest gap (10 cm) shows un-even drying indicated by various moisture content of the berries depending on location of the sample towards the IR emitter. 25 cm plat-form distance shows uniform drying effect and the average chemical proper-ties complied to Grade 1 IPC standard. The specific energy required to dry 1 kg of white pepper is 12.96 kWh/kg which considerably lower compared to the previous research. The finding is expected to address the local technological needs for white pepper drying process.